Pengaruh Electronic Word Of Mouth (E-Wom) Dan Affiliate Marketing Platform Tiktok Terhadap Minat Beli Konsumen Pada Produk Skincare Somethinc - Cindi Widayanti; Muhammad Akbar (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. The increasing prevalence of social media as a communication tool has prompted companies to adopt digital marketing strategies, such as Electronic Word of Mouth (e-WOM) and affiliate marketing, to expand their reach and enhance consumer purchase intentions. Somethinc, a local skincare brand, actively promotes its products on TikTok by partnering with affiliates and harnessing the influence of user-generated reviews. This study aimed to explore the effect of e-WOM and affiliate marketing on consumer purchase intentions. It involved 100 respondents from the Millennial and Generation Z cohorts in Central Jakarta, all of whom are active TikTok users and have encountered promotional content related to Somethinc products. The research methodology applied Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The findings show that Electronic Word of Mouth (e-WOM) and Affiliate Marketing have a positive and significant effect on Consumer Purchase Intent, with a contribution of 63.2% as indicated by the R-Square value. The analysis was conducted using the Partial Least Square (PLS) method, which produced a significant positive relationship between the two independent variables and purchase intent. Keywords: Electronic Word of Mouth (e-WOM); Affiliate Marketing; TikTok; Purchase Intentions; Somethinc